2014
DOI: 10.1007/s11356-014-3764-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A on chlorophyll synthesis in soybean seedlings

Abstract: Bisphenol A (BPA), as an emerging environmental pollutant, is potentially harmful to plant growth. Chlorophyll (Chl) is critical in photosynthesis that provides matter and energy for plant growth. How BPA affects the chlorophyll content remains largely unknown. Here, the effects of BPA on Chl synthesis in soybean seedlings were investigated. Exposure to 1.5 mg/L BPA decreased the 5-aminolevulinic acid (ALA) content and increased protoporphyrin IX (Proto IX), magnesium protoporphyrin, and protochlorophyll conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The stimulatory effect of low BPA-concentration on chlorophyll accumulation has been observed in other plants, especially in soybean seedlings (Hu et al, 2014). BPA (1.5 mg/l) increases the activity of five enzymes, involved in chlorophyll biosynthesis (Jiao et al, 2015;Jiao et al, 2017). The positive effect of BPA on chlorophyll accumulation is probably not a result of its estrogenic activities, as low-dose heavy metal concentrations also increase chlorophyll content in plants (Maleva et al, 2009;Kumar et al, 2015).…”
Section: Resultsmentioning
confidence: 79%
“…The stimulatory effect of low BPA-concentration on chlorophyll accumulation has been observed in other plants, especially in soybean seedlings (Hu et al, 2014). BPA (1.5 mg/l) increases the activity of five enzymes, involved in chlorophyll biosynthesis (Jiao et al, 2015;Jiao et al, 2017). The positive effect of BPA on chlorophyll accumulation is probably not a result of its estrogenic activities, as low-dose heavy metal concentrations also increase chlorophyll content in plants (Maleva et al, 2009;Kumar et al, 2015).…”
Section: Resultsmentioning
confidence: 79%
“…Previous research reported that the long-term leaf irrigation with BPA solution decreases chlorophyll content of leaves 6 , 7 . In this study, there is no significant change in chlorophyll content among the different treatments (Table 1 ), which indicates that the inactivation of photosynthetic apparatus (Figs 1 – 5 ) caused by BPA is independent of the degradation of pigments.…”
Section: Results and Disscussionmentioning
confidence: 96%
“…Some studies showed that the low concentrations of BPA promote the growth of soybean and carrot, however, high concentrations inhibited seed germination and root growth of broad bean, tomato, and durum wheat 5 . In addition, BPA obviously restrains the biosynthesis of chlorophyll 6 and restrains photosynthesis 7 . It also decreases the biomass of shoot, leaf area and net photosynthetic rate 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Soybean ( Glycine max , Zhonghuang 25) seeds were germinated in accordance with previously reported methods 19 . Thirty days after germination, when there were both flowers and young raised pods (approximately 2 cm) in the soybean plants, the soybean plants were transplanted into BPA solutions at different doses (0.0, 1.5, 6.0, and 12.0 mg·L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the effects of BPA on algae have been frequently reported 12 13 , but the effects of BPA on terrestrial plants are less studied 14 , and the microscopic mechanism of BPA on plants remains unclear 15 . Previous studies showed that certain doses of BPA exposure could promote or inhibit the growth 15 16 , germination 17 , pollen tube elongation 18 , photosynthesis 19 , and hormone contents 20 in plants. As a vital organ of plants in long-term adaptations to land, roots can absorb water and nutrients from soil for plant growth and development 21 , and roots also have the ability to absorb, fix and transfer pollutants.…”
mentioning
confidence: 99%